POROUS AGGREGATE DEVELOPED USING CARBONIZED CLAY FROM THE ANGREN FIELD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Object: The article is devoted to determining the optimal composition of the charge for the production of artificial porous aggregate from coal mining waste and bentonite clays, which are considered local raw materials for the development of new generations of thermal insulation and ultra-lightweight and structurally strong concrete.Methods: When developing the optimal composition of the charge for the production of porous aggregates from mineral rocks and coal mining waste, a method was used that was used as the basic theory for the production of expanded clay.Findings: Calculated and proposed formulas for the optimal composition of the charge for the production of porous aggregates appropriate for both heat-insulating (porous, ultra-light) and structural (dense, heavier) categories, despite the fact that both types of aggregates were adopted in terms of true and bulk density on lightweight (porous) aggregates.Conclusions: The optimal composition of the porous aggregate from the coal mining waste of the Angren deposits and bentonite clay from the Navbahar deposits has been determined